Simultaneous determination of the combined and free concentrations of atorvastatin and its major metabolite in vitro and in vivo based on ultraﬁltration coupled with UPLC-MS/MS method: an application in a protein binding rate and metabolism ability study in uremic hemodialysis patients - Cao, Ming-Chen; Huang, Xin; Tang, Bo-Hao; Shi, Hai-Yan; Zheng, Yi; Zhao, Wei (Frontiers in Cardiovascular Medicine, 2024)
A rapid, accurate and specific ultraﬁltration with ultra performance liquid chromatographic -tandem mass spectrometry method has been validated for the simultaneous determination of the protein binding rate of atorvastatin for uremia patients. The plasma samples were centrifuged at 6000 r/min for 15 min at 37℃ and the ultrafiltrate was collected. An ACQUITY UPLC® BEH C18 Column with gradient elution of water (0.1% formic acid) and acetonitrile was used for separation at a flow rate of 0.4 mL/min. The calibration curves of two analytes in serum showed excellent linearity over the concentration ranges of 0.05-20.00 ng/mL for atorvastatin, and 0.05-20.00 ng/mL for orth-hydroxy atorvastatin, respectively. This method was validated according to standard FDA and EMA guidelines in terms of selectivity, linearity, detection limits, matrix effects, accuracy, precision, recovery, and stability. This assay can be easily implemented in clinical practice to determine free and combined concentration of atorvastatin in uremic plasma. The final result showed that the average protein binding rate of plasma in uremic patients plasma was (86.58±2.04)%, RSD (%)=1.98, while the protein binding rate in plasma of patients with normal renal function was (97.62±1.96)%, RSD (%)=2.04, there was a significant difference in the protein binding rate of different types of plasma (P<0.05), and the protein binding rate decreases with increasing creatinine until it is stable at nearly 80%.The mean metabolite/prototype ratio of atorvastatin for patients with normal renal function and uremia were 1.085 and 0.974, respectively, suggesting that the metabolic process of atorvastatin in uremic patients may be inhibited.